Alcohol use and environmental factors: A cross-sectional study exploring health risks and social implications among Myanmar migrant workers - Kanit Hnuploy; Kittipong Sornlorm; Sameh Eltaybani; Nirachon Chutipattana (PLoS ONE, 2026)
Alcohol use poses unique challenges for migrant workers. Existing literature is limited in understanding how various determinants interact to influence health, family relationships, and social outcomes in this population. This study aims to determine the prevalence of alcohol-related impacts and examine relationships between alcohol use, environmental factors, and their broader effects among Myanmar migrant workers in Thailand. This cross-sectional study surveyed 610 Myanmar migrant workers in Thailand (Sep 2023–Mar 2024) using multi-stage sampling approach. Paper-based questionnaires were utilized, and alcohol use was assessed using the Alcohol Use Disorders Identification Test (AUDIT), with scores categorized as low-risk (0–7), risky (8–19), and probable dependence (≥20). Alcohol-related outcomes were also assessed, and generalized linear mixed models identified associated factors. Of the 610 participants, the majority were male (73.93%), with a mean age of 34.80 years (SD = 10.61) and an age range of 18–73 years. The study found that 38.20% reported a moderate level of alcohol-related impact (95% CI: 34.41–42.12), while 0.82% reported a high level (95% CI: 0.34–1.95). While alcohol addiction significantly increased adverse outcomes (AOR = 1.70, 95% CI: 1.61–1.79), environmental and occupational factors demonstrated stronger associations, with rural residency being the strongest correlate (AOR = 6.52, 95% CI: 4.35–9.77), followed by housing problems (AOR = 5.00, 95% CI: 2.70–9.24). Other significant factors included longer work hours (AOR = 2.39, 95% CI: 1.02–5.60), daily work schedules (AOR = 2.39, 95% CI: 1.64–3.49), poor sleep quality (AOR = 2.09, 95% CI: 1.51–2.90), moderate/poor health (AOR = 2.11, 95% CI: 2.02–2.22), and strained co-worker relationships (AOR = 1.89, 95% CI: 1.88–1.90). These findings highlight that environmental and occupational factors are more strongly associated with alcohol-related impacts than alcohol dependence itself, supporting public health strategies that address structural conditions alongside individual-level interventions.